Računalniško upravljanje z obdelovalnimi orodji v orodjarni, podprto s simulacijo - Debevec, Mihael (Strojniški vestnik, 2003)
With the exception of maschining centers, cutting tools are the most expensive items in the production costs of a tool-making company. Unorganised warehousing and poor monitoring of the condition of the cutting tools are still typical of such companies, and this results in the underhouse of machining centres and high costs for the cutting tools. By using well-organized and computerized tool management of the cutting tools it is possible to reduce costs, but for the efficient planning of production this is still not enough. In this article we introduce the concept of Simulation-Aided Tool Management (SATM) and the main features of the SATM system, which was developed in cooperation with a tool-making company.
Keywords: sistemi upravljalni; baze podatkov; proizvodnja; simuliranje; mreže Petri; rezalna orodja; management; upravljanje; avtomatizacija; simulacija; Petrijeve mreže